Activities of nine antifungal agents against Candida auris biofilms. Issue 4 (13th December 2020) - Chatzimoschou, Athanasios; Giampani, Athina; Meis, Jacques F.; Roilides, Emmanuel
Abstract: Background: Candida auris is a newly described multidrug‐resistant fungal pathogen associated with biofilm formation and severe infections with high mortality. Objectives: To study the activities of fluconazole, itraconazole, posaconazole, voriconazole, deoxycholate and liposomal amphotericin B, anidulafungin, caspofungin and micafungin against C auris biofilms and planktonic cells. Materials/Methods: C auris strains originating from 5 clades (South Asian, East Asian, African, South American and Iranian) were tested for biofilm production by safranin staining of the extracellular matrix polysaccharide structure as well as biofilm (BF) and planktonic (PLK) antifungal susceptibility to nine antifungal agents using the XTT reduction assay. Results: Candida auris isolates produced mature BF as compared to non‐ C auris control ( Candida albicans and Candida parapsilosis) strains. Four C auris isolates exhibited relatively high MIC's for fluconazole (32–128 mg/L for PLK MIC and 128–1024 mg/L for BF MIC) as compared to the Iranian strain that had PLK and BF MIC's 0.5 and 16, respectively. Itraconazole, posaconazole and voriconazole had relatively low PLK MICs but high BF MICs. A similar pattern was observed with echinocandins; relatively low PLK MIC (0.06–4 mg/L) but quite high BF MICs (4–2048 mg/L). While all isolates exhibited relatively low PLK MICs (0.06–4 mg/L) for both amphotericin B formulations, liposomal amphotericin B showed higher MICs compared to deoxycholate amphotericin B against C auris BF. Conclusion: Triazoles, echinocandins and liposomal amphotericin B appear to have less activity against C auris biofilms than deoxycholate amphotericin B. Our in vitro model provides evidence for intrinsic C auris biofilm resistance to antifungal agents.